Progress in antibacterial applications of nanozymes - Zhao, Keyuan; Zhao, Ye; Wang, Yuwei; Han, Bo; Lian, Meiling (Frontiers in Chemistry, 2024)
Bacterial infections are a growing problem, and antibiotic drugs can be widely used to fight bacterial infections. However, the overuse of antibiotics and the evolution of bacteria have led to the emergence of drug-resistant bacteria, severely reducing the effectiveness of treatment. Therefore, it is very important to develop new effective antibacterial strategies to fight multi-drug resistant bacteria. Nanozyme is a kind of enzyme-like catalytic nanomaterials with unique physical and chemical properties, high stability, structural diversity, adjustable catalytic activity, low cost, easy storage and so on. In addition, nanozymes also have excellent broad-spectrum antibacterial properties and good biocompatibility, showing broad application prospects in the field of antibacterial. In this paper, we reviewed the research progress of antibacterial application of nanozymes. At first, the antibacterial mechanism of nanozymes was summarized, and then the application of nanozymes in antibacterial was introduced. Finally, the challenges of the application of antibacterial nanozymes were discussed, and the development prospect of antibacterial nanozymes was clarified.